Resetting the circadian clock of Alzheimer’s mice via GLP-1 injection combined with time-restricted feeding - Dong, Yanqiong; Cheng, Le; Zhao, Yingying (Frontiers in Physiology, 2022)
Alzheimer's disease (AD) is a complex, irreversible neurodegenerative disease characterized by impaired cognitive functions and alteration of personality and behavior. Circadian rhythm disturbances are the most common symptoms in the early onset of AD. Circadian rhythm disorders aggravate the deposition of amyloid plaques in the brains of AD patients. Therefore, improving the circadian rhythm of AD patients might slow down the pathological development of neurodegeneration. Circadian regulation is driven by a master clock in suprachiasmatic nuclei (SCN) and peripheral clock located in peripheral organs. Rhythmic feeding-fasting cycle has been proved to dominant cue to entrain peripheral clocks. We hypothesized that dietary intervention to a certain period of time during the dark phase might entrain the clock and reset the disrupted daily rhythms of AD mice. In this study, exogenous glucagon-like peptide-1 (GLP-1) treatment, time-restricted feeding (TRF) and the combination were used to examine the effect of overall circadian rhythm and neurodegenerative pathogenesis of transgenic AD mice. It was confirmed that GLP-1 administration together with time-restricted feeding improve circadian rhythm of 5xFAD mice including the physiological rhythm of activity-rest cycle, feeding-fasting cycle, core body temperature and hormone secretion. Furthermore, GLP-1 and TRF treatments improved the diurnal metabolic homeostasis, spatial cognition and learning of 5xFAD mice. Abnormal expression of clock genes, including Baml1, Clock and Dbp were improved in hypothalamus, and ameliorated pathogenesis of neurodegeneration was also observed in AD mice with dual treatment.